2009
DOI: 10.1007/s10295-009-0653-5
|View full text |Cite
|
Sign up to set email alerts
|

Variations of bacterial 16S rDNA phylotypes prior to and after chlorination for drinking water production from two surface water treatment plants

Abstract: We examined the variations of bacterial populations in treated drinking water prior to and after the final chlorine disinfection step at two different surface water treatment plants. For this purpose, the bacterial communities present in treated water were sampled after granular activated carbon (GAC) filtration and chlorine disinfection from two drinking water treatment plants supplying the city of Paris (France). Samples were analyzed after genomic DNA extraction, polymerase chain reaction (PCR) amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 51 publications
4
44
0
2
Order By: Relevance
“…Using culture-dependent technique, Norton and LeChevallier (2000) found that Pseudomonas (affiliated with Gammaproteobacteria) and Sphingomonas (affiliated with Alphaproteobacteria) were the predominant isolates in the BAC filter effluent. A recent study using clone library analysis indicated that Alphaproteobacteria and Betaproteobacteria were predominant in the BAC filter effluent (Poitelon et al 2010). In this study, Alphaproteobacteria, Betaproteobacteria, and Actinobacteria were found to be major bacterial groups in the BAC filter effluent.…”
Section: Bacterial Community Structuressupporting
confidence: 47%
See 4 more Smart Citations
“…Using culture-dependent technique, Norton and LeChevallier (2000) found that Pseudomonas (affiliated with Gammaproteobacteria) and Sphingomonas (affiliated with Alphaproteobacteria) were the predominant isolates in the BAC filter effluent. A recent study using clone library analysis indicated that Alphaproteobacteria and Betaproteobacteria were predominant in the BAC filter effluent (Poitelon et al 2010). In this study, Alphaproteobacteria, Betaproteobacteria, and Actinobacteria were found to be major bacterial groups in the BAC filter effluent.…”
Section: Bacterial Community Structuressupporting
confidence: 47%
“…The bar represents 1 % sequence divergence DWDs (Lu et al 2013). Moreover, the composition of the bacterial community in chlorinated (or chloraminated) water might be much different from that in non-chlorinated (or non-chloraminated) water (Norton and LeChevallier 2000;Berry et al 2006;Eichler et al 2006;Kormas et al 2010;Poitelon et al 2010). Unfortunately, very few research works have provided the phylogenetic description of bacterial community in the sand filter effluent and the BAC filter effluent.…”
Section: Bacterial Community Structuresmentioning
confidence: 99%
See 3 more Smart Citations